The HRM Transition in Kazakhstani Local Companies - Bermukhamedova, Zarina (2016)
The purpose of this paper is to discover whether Human Resource Management or Personnel Management practices are being applied in Kazakhstani local companies along with finding out the challenges of being contemporary with global trends and implementing HRM policies. The target audience for the study are local top – managers and HR practitioners of all levels; as both groups should to have a realistic view of the HR positioning in local companies and insight on the challenges of the HRM practices implementation. The study presents a detailed understanding of people management approach by the HR managers and the type of HR management practices used in local companies, which led to the conclusion that people management approach in indigenous Kazakhstani firms is on the transition stage towards HRM paradigm. The paper also presents major and minor challenges of this transition, provided by participants. Some recommendations for the more effective and productive HR management in Kazakhstani local organizations were provided on the basis of the respondents’ insightful view and knowledge of the situation.